Gay on God's campus : mobilizing for LGBT equality at Christian colleges and universities - Coley, Jonathan S. (Chapel Hill : University of North Carolina Press, 2018)
"Jonathan Coley explores the unique pathways along which students join and work within movements for LGBT inclusion at Christian institutions of higher learning across the country. Having interviewed dozens of students in LGBT advocacy groups at four conservative, religious schools of different denominations, Coley is able to use students' own words to analyze their self-conceptions and activist tactics, while shedding new light on faith-based LGBT activism on college campuses. Moreover, Coley shows that there is no single pathway to activism and, perhaps most importantly, that religion and pro-LGBT activism are not mutually exclusive categories"--
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (EBSCO, viewed February 6, 2018).
Master record variable field(s) change: 072
Keywords: Gay college students -- Political activity -- United States; Christian college students -- Political activity -- United States; Student movements -- United States; Sexual minorities -- Political activity -- United States; EDUCATION / Higher; SOCIAL SCIENCE / Gay Studies; Electronic books